Plan of joint action for agricultural reactivation in Latin America and the Caribbean. The case of Haití - Instituto Interamericano de Cooperación para la Agricultura (IICA) (1989)
Serie Plan of Joint Action for Agricultural Reactivation in Latin America and the Caribbean no. 8.